Regeneration of Abies Alba Mill. On the territory of the Polessky state forestry - Ermakov Sergei; Zhigunov Anatoly; Belousova Polina (BIO Web of Conferences)
Abies alba Mill. is a breed planted for initial introduction testing more than 120 years ago on the territory of East Prussia, now the Kaliningrad region, and have the interest to evaluate the results of the introduction. The assessment of taxation indicators was carried out with clarification of the individual trees age, storiness of forest, the sanitary condition, the presence and determination of the species composition of related species, the composition of the undergrowth, the presence of young undergrowth and assessment of its conditions, the presence and abundance of self-seeding. The characteristic of soils and ground cover is given. In the studied area, the type of forest conditions is C 2, the type of forest is sour fir. Two age groups of A. alba were identified within the quarter: the initially laid culture consists of specimens about 100 years old (h 35.5 m) and form 1 layer. The second generation forms the second layer these are specimens about 50 years old (h 28m). Related rocks in the surveyed area are Quercus robur L., Fagus sylvatica L., Quercus rubra L., Betula pendula Roth., Picea abies. The composition of the second layer is expressed by the formula 7A(b)2B1F+Or+Oe+Bh. A. alba has a massive undergrowth forming scattered group of young undergrowth from 1 to 3 m high, in addition to it, young undergrowth of the above-mentioned species is present in the composition. The available self-seeding with strong variability averages about 48 pcs/m2. In the studied area, the A. alba plantation develops according to the Ist bonitet, has good seedling, seedlings are quite viable and abundant, persist and successfully survive without human intervention. Undergrowth and self-seeding occur not only directly under the crown cover of mother trees, but also at great distances from fruiting specimens. Good growth and development of the introduced A. alba is at the same time a factor that increases the likelihood of death of age-related specimens and suppression of undergrowth of P.abies, the main concomitant and competitive breed.